Competitiveness of the company's personnel: evaluation factors - Pohorielova, T. O.; Suslikov, S. V.; Pererva, P. G. (Видавничий дім "Києво-Могилянська академія", 2023)
The formation and development of competitive advantages of personnel is determined by multi-level, interrelated factors. In addition to competitive advantages, competitiveness is influenced by other factors. For example, the market, its size and growth rate, the larger it is, the stronger the struggle "for a place under the sun"; obstacles to entering the market; price; power; requirements, etc.
Конкурентоспроможність персоналу підприємства: фактори оцінки
Keywords: competitiveness of personnel; assessment; market; demand; supply; price